2021
DOI: 10.3390/cells10113126
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics Reveals the Expression of Aging- and Senescence-Associated Genes in Distinct Cancer Cell Populations

Abstract: The human aging process is associated with molecular changes and cellular degeneration, resulting in a significant increase in cancer incidence with age. Despite their potential correlation, the relationship between cancer- and ageing-related transcriptional changes is largely unknown. In this study, we aimed to analyze aging-associated transcriptional patterns in publicly available bulk mRNA-seq and single-cell RNA-seq (scRNA-seq) datasets for chronic myelogenous leukemia (CML), colorectal cancer (CRC), hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 111 publications
(161 reference statements)
0
17
0
Order By: Relevance
“…( B ) Gene ontology (GO Biological Process, EnrichR [ 16 ]) revealed that SNP-containing loci (purple), genes upregulated in CD (green) and their overlap (teal) are related to inflammatory pathways, while genes downregulated in CD (red) and their overlap with SNP-containing regions (dark red) are not. ( C ) Dot plot depicting cell types related to CD-induced genes according to PanglaoDB Augmented 2021 [ 17 ]. The dot color reflects a combination of p -value and z-score, referred to as combined score, whereas the dot size correlates to the number of enriched genes.…”
Section: Figurementioning
confidence: 99%
“…( B ) Gene ontology (GO Biological Process, EnrichR [ 16 ]) revealed that SNP-containing loci (purple), genes upregulated in CD (green) and their overlap (teal) are related to inflammatory pathways, while genes downregulated in CD (red) and their overlap with SNP-containing regions (dark red) are not. ( C ) Dot plot depicting cell types related to CD-induced genes according to PanglaoDB Augmented 2021 [ 17 ]. The dot color reflects a combination of p -value and z-score, referred to as combined score, whereas the dot size correlates to the number of enriched genes.…”
Section: Figurementioning
confidence: 99%
“…We followed the protocol described by Dominik Saul et al [ 61 ] to identify aging/senescence-induced genes and characterize the molecular patterns associated with cellular senescence. A total of 1535 aging/senescence-inducing genes were identified in 17 databases or studies, and a total of 1153 genes remained after deduplication.…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in pathways of senescence, such as CDKN2A and TP53, and deficiencies in apoptotic pathways (i.e., inactivation of the CD95 receptor/ligand system) are frequently involved cancer cells ( Debatin, 2004 ; Hanahan and Weinberg, 2011 ; Park et al, 2021 ). Combined heterogeneity at the cellular and molecular levels may thus mediate the dynamics of diverse cancer cell subpopulations that exhibit deregulation of gene expression associated with age senescence ( Jochems et al, 2021 ; Saul and Kosinsky, 2021 ). In this regard, transcriptional heterogeneity and diversity in senescent cells warrants further investigation into their clinical relevance in cancer ( Davis-Marcisak et al, 2021 ; Faget et al, 2019 ; Nicos et al, 2020 ).…”
Section: Transcriptional Heterogeneity Of Sasp In Malignancymentioning
confidence: 99%
“…By understanding the complex SASP-receptor communication and molecular signaling networks supporting the expression of various novel SA genes in cancer cells, we may overcome cancer therapy resistance ( Chambers et al, 2021 ). Recently, Saul and Kosinsky (2021) identified the expression of various senescence-associated genes in distinct cancer cell populations from mouse tissue, providing the basis for future studies on the role of senescence in the development of specific tumor types in human cells. More comprehensive comparisons are thus needed between various cancer types and their single-cell profiles to enable widespread use of single-cell technologies for biomarker discovery and therapeutic intervention.…”
Section: Transcriptional Heterogeneity Of Sasp In Malignancymentioning
confidence: 99%
See 1 more Smart Citation